Community Policing by Police Intelligence: Analysis on the Empowerment of Islamic Organization in Preventing the Spread of Radical Islamic Movement - Hafiz Prasetia Akbar; Surya Nita (Budapest International Research and Critics University, 2022)
Police intelligence has not been known to conduct visible policing strategies such as community policing. However, this research has proven that the intelligence unit, through network building, has inherently the same concept as community policing. Community policing through police intelligence could reach issues uniformed police are deemed too sensitive to approach, such as radicalism. By empowering Islamic Organizations, they can have the power to prevent the spread of radical Islamic movements in Indonesia. Therefore, this research was conducted to analyze the empowerment of Islamic Organizations carried out by the Police Intelligence Unit by doing a case study in West Bandung. This research was conducted with a qualitative approach using descriptive research methods and data collection techniques with interviews, observations, and document studies. The study results found that the empowerment had been carried out but was not optimal. It is found that the intelligence unit does not understand the procedures for implementing community policing because there is no organizational procedure and limited organizational capability. Moreover, political, social, technological and natural factors also negatively influence community policing by police intelligence.